'I do not envy you': Mixed marriages and immigration debates in the 1920s and 1930s Rangoon, Burma. (October 2014) - Mazumder, Rajashree
This article uses the mixed marriage debate in 1920s and 1930s Rangoon as a lens to understand how the figure of the Indian immigrant was created in the official discourse and popular imagination in Burma.As the discussion on mixed marriages unfolded amongst lawmakers and in the Burmese public sphere in the early twentieth century, it perpetuated the stereotype of the avaricious Burmese woman and the Indian was portrayed as a single male temporary worker who was in Burma for employment and left the woman once he returned back home. The problem of abandoned women as a result of inter-racial marriages was, in reality, a larger problem of Indian immigration into Burma. In 1940, with the Indo-Burmese immigration agreement, marriage or cohabitation between Indian male immigrant and women belonging to the indigenous races of Burma was made a condition for cancellation of a permit or visa granted to a migrant Indian male.